PENERAPAN MODEL PEMBELAJARAN KOOPERATIF JIGSAW UNTUK MENINGKATKAN MOTIVASI PADA SISWA KELAS V SEKOLAH DASAR - Bandi Usman; Khairil Akbar; Kurnia Dyah Anggorowati (STKIP Melawi, 2020)
Abstrak: This study aims to increase student learning motivation in the field of physical education, sports and health. The learning model used is the application of the learning model through cooperative jigsaw to increase learning motivation in the field of physical education, sports and healthfor fifth grade students. Classroom action research (PTK) is carriedout using data collection techniques, namely motivation tests and questionnaires. The results of this study showed that in cycle 1, the average value of student learning motivation was 73% in the motivated category but not yet complete. Then in cycle II obtained a percentage of learning motivation of 90% categorized as motivated according to the success criteria and seen from the point of view of the maximum completeness criteria (KKM) students are said to be complete. The percentage of increasing learning motivation from cycle I to cycle II was 17%. The jigsaw cooperative learning model can increase student motivation, especially in sports and health physical education subjects.Keywords: learning Model, motivation to learn physical education sports and health.Abstrak: Penelitian ini bertujuan untuk meningkatkan motivasi belajar siswa pada bidang studi Pendidikan Jasmani Olahraga dan Kesehatan. Model pembelajaran yang digunakan adalah penerapan model pembelajaran melalui kooperatif Jigsaw untuk meningkatkan motivasi belajar pada bidang studi Pendidikan Jasmani Olahraga dan Kesehatan pada siswa kelas V, dilakukan penelitian tindakan kelas (PTK) dengan teknik pengumpulan data yakni tes dan angket motivasi. Hasil penelitian ini diperoleh siklus I nilai rata-rata motivasi belajar siswa presentase sebesar 73% kategori termotivasi tetapi belum tuntas. Kemudian pada siklus II diperoleh presentase motivasi belajar sebesar 90% dikategorikan termotivasi sesuai kriteria keberhasilan dan dilihat dari sudut pandang kriteria ketuntasan maksimal (KKM) siswa sudah dikatakan tuntas. Presentase peningkatan motivasi belajar siklus I ke siklus II yaitu 17%. Model pembelajaran kooperatif jigsaw dapat meningkatkan motivasi belajar siswa, terutama pada mata pelajaran Pendidikan Jasmani Olahraga dan Kesehatan.Kata Kunci: Model Pembelajaran, Motivasi Belajar Pendidikan Jasmani Olahraga dan Kesehatan